Analysis of Police and Customs Technology in Combating Illegal Cigarettes in Indonesia - Isnawan, Fuadi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 1 (2025), 2025)
his study aims to explore the role of police technology, particularly through the use of cyber patrols and cyber police, in detecting, cracking down on, and suppressing the circulation of illegal cigarettes in Indonesia, as well as how technology can serve as a preventive effort to reduce the distribution of illegal cigarettes. This normative study focuses on the analysis of relevant legal regulations and policies. The novelty of this research lies in its emphasis on the role of police technology, specifically through cyber patrol and cyber police operations, in combating the illegal circulation of cigarettes, introducing new perspectives to fill existing gaps in the literature. The findings reveal that the role of police technology, particularly through the operations of cyber police and cyber patrol units, has become increasingly critical in detecting, cracking down on, and suppressing the circulation of illegal cigarettes in Indonesia. Law enforcement’s adaptability to the evolving digital landscape is essential in addressing crimes facilitated by e-commerce and social media as channels for illicit cigarette trade. By employing cyber surveillance, digital tracking, and coordinated online efforts, the Indonesian National Police and specialized cyber units have developed effective strategies to mitigate these illegal activities. Preventive efforts also include educational initiatives and digital campaigns on social media to raise public legal awareness and compliance. The innovative use of digital tools such as the Illegal Cigarette Information System (SIROLEG) exemplifies technological integration in optimizing reporting and coordination among enforcement units. This study concludes that strategic technological interventions offer a holistic, effective framework for addressing the complex challenges posed by the illegal tobacco trade in Indonesia.